BUDAYA KERJA GURU BERSERTIFIKASI (Studi Situs SMP Negeri 2 Kaliwungu Kendal) - HARTANTO , HARTANTO (2011)
This study is aimed at to describe the working culture of administration, teaching learning activities, and evaluating of the teaching learning process accelerates to the class of SMP Negeri 2 Kaliwungu teachers in doing their jobs. This study applies the qualitative of ethnographic to see directly the working culture of the subject of the study such as their behavior, their motivation, their perception and their action. It relates with good teachers in working culture. The datas are taken from interviews with some teachers, the documents related of the teacher's jobs, and field study. By collecting the datas, the researcher carried out interview with teachers, doing some observations, and study the documents related to the professional teacher's job. The datas are analyzed and tested using credibility, dependability, and confirmability tests. The result of the study shows: (1) the professional teachers working culture in doing their administrative means how a teacher increases working culture such as developing syllabus, making lesson plan, developing indicators, and developing teacher's materials. The professional teacher's working culture appointed in their administration work of developing in the school and regional teacher forum; (2) the profesional teachers working culture in teaching learning activities means how a teacher increases working culture such as, introduction activity, core activity, and final activity in the teaching and learning process in order to be correct and fluent appropriate by the curriculum. (3) the professional teachers working culture in evaluating of the the teaching learning process means how a teacher increases working culture such as compilation planning of assessment and execution of assessment.